Do dekonstrukcji i z powrotem - Agata Bielik-Robson (Przestrzenie Teorii)
The concept of the turn belongs to the favourite terms of nowadays humanities. The so called "deconstructive turn" became one of their most cherished cliches, which, as a cliche, immediately calls for a sceptical, typically deconstructionist intervention. In my paper, I question radically of the deconstructive project by trying to show that deconstruction, despite all the slogans it produced, proclaiming the death of the author and the subject, is far more continuous with modern tradition than it is commonly assumed. Especially, the notion of subjectivity is the one which most stubbornly resists the deconstructive attempts of its "undoing". I analyse three strategies of deconstruction, created by Paul de Man, Jacques Derrida and Harold Bloom, and conclude by pointing to the dialectical circle based on the concepts of expression and inscription. The traditional "romantic" subject perceives itself as an expressive voice for which writing is merely a secondary means of expression. Deconstruction of de Man and Derrida overturns the "romantic" subject by demonstrating the primacy of the effect of inscription. But the postdeconstructive work of Harold Bloom shows the possibility of reconciliation between expression and inscription which opens the way for the return of the subject, although no longer traditionally conceived.